The Portrayal of Women in P!nk's and The Pussycat Dolls' Albums in the View of Postfeminism - Fuad, Maulana Subhan (2014)
This present study entitled The Portrayal of Women in P!nk's and The Pussycat Dolls' Albums in the View of Postfeminism is aimed at unearthing the patterns which are acquired after analysing the portrayal of female personas in every single song lyrics that possesses the characteristics of postfeminism in P!nk's Funhouse and The Pussycat Dolls' Doll Domination. Using a qualitative method, particularly textual analysis, the discussion of the present study is framed within theory of backlash postfeminism (Faludi, 1991) and popular culture (Magoulick, 2006). The study proves that the pattern in P!nk's is more visible than in The Pussycat Dolls' one because it possesses all of the characteristics of postfeminism. Moreover, although both of the female personas in their albums share the same characteristics, the study shows that the way the female personas are described is different from each other. Overall, the female personas are portrayed as women who reject the notion of feminism in the form of being individual, returning to men, suffering from female identity crisis, and experiencing self doubt. However, these kinds of women's portrayals support the idea of the bad representation of women in popular culture. It is explained that women tend to be depicted wrongly for being true to themselves as in desiring to have a romantic relationship with men and be happy about it without any compulsions.